The Effect of Educational Video on the Implementation of a Healthy Lifestyle for the Prevention of Gestational Diabetes in Pregnant Women - Elizar Elizar; Nurmila Nurmila; Hendrika Wijaya Kartini Putri; Kartinazahri Kartinazahri; Elit Pebryatie; Endang Nurrochmi (Ann Publisher, 2026)
Background, Gestational Diabetes Mellitus (GDM) is an increasingly common pregnancy complication associated with macrosomia, preeclampsia, and later type 2 diabetes, and healthy lifestyle modification is its primary prevention strategy, yet uptake among pregnant women remains low due to limited practical educational media. Aim, This study aimed to analyze the effect of educational videos on the implementation of a healthy lifestyle for the prevention of gestational diabetes among pregnant women in the working area of the Lhokseumawe City Community Health Center Methods, A quantitative quasi-experimental study with a non-equivalent control group design was conducted on 64 pregnant women (32 intervention, 32 control), selected through purposive sampling; data were collected with a modified questionnaire before and two weeks after the intervention and analyzed using the Wilcoxon Signed Ranks and Mann-Whitney U tests Results, Both groups improved significantly after the intervention, but the increase in the intervention group was significantly greater than in the control group (mean rank 34.17 versus 25.83; p<0.001). Conclusions, Educational videos were more effective than leaflets and lectures in improving healthy lifestyle implementation. Implication. Health workers should integrate educational videos into routine antenatal care to support the prevention of gestational diabetes